Toward a Latino/a biblical interpretation - Lozada, Francisco (Resources for biblical study, 2017)
Introduction: theorizing Latino/a biblical interpretation -- Toward Latino/a biblical studies: foregrounding identities and transforming communities -- Journeys and the Fourth Gospel: a correlation strategy -- Matthew 6:9b-13 (the Lord's Prayer): a dialogical strategy -- Galatians 2:11-14; an ideological strategy -- Conclusion: Latino/a biblical interpretation: is it a question of being and/or practice?